Geometric accuracy by 2-D printing model - Galeta, Tomislav (Strojniški vestnik, 2008)
In order to improve the accuracy of three-dimensional printing (3DP), we carried out a set of experiments on two-dimensional (2-D) printed model. The combinations of three main processing factors were considered for every experiment: layer thickness, building orientation and infiltrant type. The results of experiments provided the appropriate anisotropic scale factor and proved the adequacy of anisotropic scaling. The analysis of results indicates that smaller layer thickness, infiltration with epoxy resin and sample orientation towards building direction of X axis provide better sample accuracy.
Keywords: tiskanje; prototipi; natančnost